Para-Aminosalicylic acid is a prodrug targeting dihydrofolate reductase in Mycobacterium tuberculosis33991 - Zheng,J.; Rubin,E.J.; Bifani,P.; Vanessa Mathys; Lim,V.; Au,M.; Jang,J.; Nam,J.; Dick,T.; Walker,J.R.; Pethe,K.; L. Camacho (J.Biol.Chem., 2013)
para-Aminosalicylic acid (PAS) is one of the antimycobacterial drugs currently used for multidrug-resistant tuberculosis. Although it has been in clinical use for over 60 years, its mechanism(s) of action remains elusive. Here we report that PAS is a prodrug targeting dihydrofolate reductase (DHFR) through an unusual and novel mechanism of action. We provide evidences that PAS is incorporated into the folate pathway by dihydropteroate synthase (DHPS) and dihydrofolate synthase (DHFS) to generate a hydroxyl dihydrofolate antimetabolite, which in turn inhibits DHFR enzymatic activity. Interestingly, PAS is recognized by DHPS as efficiently as its natural substrate para-amino benzoic acid. Chemical inhibition of DHPS or mutation in DHFS prevents the formation of the antimetabolite, thereby conferring resistance to PAS. In addition, we identified a bifunctional enzyme (riboflavin biosynthesis protein (RibD)), a putative functional analog of DHFR in a knock-out strain. This finding is further supported by the identification of PAS-resistant clinical isolates encoding a RibD overexpression mutation displaying cross-resistance to genuine DHFR inhibitors. Our findings reveal that a metabolite of PAS inhibits DHFR in the folate pathway. RibD was shown to act as a functional analog of DHFR, and as for DHFS, both were shown to be associated in PAS resistance in laboratory strains and clinical isolates
Keywords: 0; a; acid; Activity; Agent; Agents; Aminosalicylic Acid; an; antagonists & inhibitors; Antitubercular Agents; article; AS; Bacterial Proteins; Benzoic Acid; biosynthesis; Clinical; Dihydropteroate Synthase; disease; Diseases; DRUG; drugs; electronic; evidence; Folate; Folic Acid; Folic Acid Antagonists; Folic-acid; Functional; Gene Knockdown Techniques; genetics; identification; im; Institute; IS; IT; journal; Laboratories; mechanism; metabolism; Mutation; Mycobacterium; Mycobacterium tuberculosis; Pa; PAS; pharmacokinetics; pharmacology; prevent; Prodrugs; protein; Proteins; report; Research; Research Support; resistance; SB - IM; strain; Tetrahydrofolate Dehydrogenase; Tuberculosis; use